2019
DOI: 10.5492/wjccm.v8.i6.87
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation with direct thrombin inhibitors during extracorporeal membrane oxygenation

Abstract: Use of extracorporeal membrane oxygenation to support patients with critical cardiorespiratory illness is increasing. Systemic anticoagulation is an essential element in the care of extracorporeal membrane oxygenation patients. While unfractionated heparin is the most commonly used agent, unfractionated heparin is associated with several unique complications that can be catastrophic in critically ill patients, including heparin-induced thrombocytopenia and acquired antithrombin deficiency. These complications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 51 publications
0
71
2
Order By: Relevance
“…Patients on V-A ECMO are more likely to experience severe thrombocytopenia and arterial thromboembolism; those on V-V ECMO are more likely to require device or circuit exchange due to oxygenator thromboembolism [32]. Direct thrombin inhibitors (DTIs) have received signi cant attention in recent years with preference towards argatroban and bivalirudin [11,12,33]. Bivalirudin has a half life of approximately 25 minutes, which may be a limitation in areas of blood stagnation, especially during V-A ECMO with non-pulsatile ow [34].…”
Section: Discussionmentioning
confidence: 99%
“…Patients on V-A ECMO are more likely to experience severe thrombocytopenia and arterial thromboembolism; those on V-V ECMO are more likely to require device or circuit exchange due to oxygenator thromboembolism [32]. Direct thrombin inhibitors (DTIs) have received signi cant attention in recent years with preference towards argatroban and bivalirudin [11,12,33]. Bivalirudin has a half life of approximately 25 minutes, which may be a limitation in areas of blood stagnation, especially during V-A ECMO with non-pulsatile ow [34].…”
Section: Discussionmentioning
confidence: 99%
“…This literature review revealed five studies, four of them concerning DTIs. DTIs have advantages over UFH, including direct binding of both circulating and clot-bound thrombin, resulting in increased efficacy compared to UFH, antithrombin independence and no risk of heparin-induced thrombocytopenia (41). Bivalirudin is the most commonly used alternative for UFH in pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its largely organ-independent metabolism, bivalirudin has a short half-life of 25 minutes in patients with normal renal function. 6,18 Other reported benefits of this drug class, when compared with heparin, include the ability to inhibit circulating and clot-bound thrombin and the absence of association with HIT. 18 Sepsis and acute respiratory distress syndrome, including COVID-19, are characterized by a procoagulant state that results in a massive production of thrombin.…”
Section: Discussionmentioning
confidence: 99%
“…6,18 Other reported benefits of this drug class, when compared with heparin, include the ability to inhibit circulating and clot-bound thrombin and the absence of association with HIT. 18 Sepsis and acute respiratory distress syndrome, including COVID-19, are characterized by a procoagulant state that results in a massive production of thrombin. 19 In addition to direct effects on the endothelial barrier by thrombin, the subsequent cleavage of fibrinogen to fibrin results in diffuse alveolar and interstitial fibrin deposition yielding the formation of microthrombi.…”
Section: Discussionmentioning
confidence: 99%